Resonance of Climate Crisis News Discourse in Indonesian Online Media: Reflections on Niklas Luhmann's Ecological Communication Theory Perspective - Astuti, Erika Febri; Inayah, Fitriana; Dahana, Abyzan Syahadin Bagja (CHANNEL: Jurnal Komunikasi, 2024)
Indonesia, an archipelago significantly vulnerable to the climate crisis, faces numerous natural disasters impacting various sectors. Despite the critical need for public awareness and proactive measures, media coverage of climate crisis issues in Indonesia remains limited. This study investigates the level of resonance in online media reporting on the climate crisis from January to December 2023, focusing on keywords related to climate change, forest fires, and air pollution. The research uses topic modeling and Niklas Luhmann's systems theory to examine how four major Indonesian online media outlets address climate crisis issues. The findings reveal that while kompas.com and detik.com show consistent coverage, ANTARA and CNBC Indonesia place less emphasis on these topics. The study highlights the need for enhanced and more impactful media coverage to raise public awareness and drive meaningful action against the climate crisis. The results underscore the importance of media collaboration with governments, NGOs, and communities to increase the resonance of climate crisis issues in public discourse. Future research should explore the reasons behind the variation in media coverage and its impact on public perception and policy decisions, including the role of social media platforms.